A dual role for glutathione transferase U7 in plant growth and protection from methyl viologen-induced oxidative stress. Issue 4 (21st September 2021) - Ugalde, José Manuel; Lamig, Liliana; Herrera-Vásquez, Ariel; Fuchs, Philippe; Homagk, Maria; Kopriva, Stanislav; Müller-Schüssele, Stefanie J; Holuigue, Loreto; Meyer, Andreas J
Abstract: Plant glutathione S -transferases (GSTs) are glutathione-dependent enzymes with versatile functions, mainly related to detoxification of electrophilic xenobiotics and peroxides. The Arabidopsis ( Arabidopsis thaliana ) genome codes for 53 GSTs, divided into seven subclasses; however, understanding of their precise functions is limited. A recent study showed that class II TGA transcription factors TGA2, TGA5, and TGA6 are essential for tolerance of UV-B-induced oxidative stress and that this tolerance is associated with an antioxidative function of cytosolic tau-GSTs (GSTUs). Specifically, TGA2 controls the expression of several GSTUs under UV-B light, and constitutive expression of GSTU7 in the tga256 triple mutant is sufficient to revert the UV-B-susceptible phenotype of tga256 . To further study the function of GSTU7, we characterized its role in mitigation of oxidative damage caused by the herbicide methyl viologen (MV). Under non-stress conditions, gstu7 null mutants were smaller than wild-type (WT) plants and delayed in the onset of the MV-induced antioxidative response, which led to accumulation of hydrogen peroxide and diminished seedling survival. Complementation of gstu7 by constitutive expression of GSTU7 rescued these phenotypes. Furthermore, live monitoring of the glutathione redox potential in intact cells with the fluorescent probe Grx1-roGFP2 revealed that GSTU7 overexpression completely abolished the MV-induced oxidation of the cytosolic glutathione buffer compared with WT plants. GSTU7 acted as a glutathione peroxidase able to complement the lack of peroxidase-type GSTs in yeast. Together, these findings show that GSTU7 is crucial in the antioxidative response by limiting oxidative damage and thus contributes to oxidative stress resistance in the cell. Abstract : Deletion of cytosolic glutathione transferase U7 in Arabidopsis causes delayed growth and development and renders mutants hypersensitive to oxidative stress induced by the herbicide methyl viologen.